Spice price spikes: Simulating gendered impacts of a saffron boom and bust in rural Morocco - Filipski, Mateusz J. (2015)
Access to international markets provides smallholders with unprecedented opportunities, but also exposes them to market whims of unprecedented amplitude and can trigger substantial changes in the local economy. In Morocco’s mountainous Taliouine-Taznakht region, saffron production drives the local economy and is the major source of female employment. The global market for saffron has been excessively volatile lately. We use a local economy-wide impact evaluation (LEWIE) approach to reveal how saffron price shocks reverberate through the local economy, with a particular focus on gender impacts. We find that saffron price shocks dramatically affect saffron production and labor demand, particularly for female harvest labor. Investments in yield-enhancing technologies create harvest labor bottlenecks that disproportionately affect women. Using Monte Carlo methods show that variability in female wage income is especially sensitive to variability in global saffron prices. Appreciating local inter-linkages is critical to understand household and regional impacts of export price volatility. Filipski, Mateusz; Aboudrare, Abdellah; Lybbert, Travis J.; Taylor, J. Edward